Hibridisasi Masyarakat Tionghoa di Kecamatan Lasem Pasca-Reformasi - Mochamad Iqbal Jatmiko (Umbara, 2019)
Chinese descendants in Indonesia, known as Tionghoa, have suffered from discrimination since the New Order regime, ranging from policy to identity status. The discrimination reached its peak in May 1998 as the riots blew up against Chinese descendants. The riots have been a footage of dark history that destroyed the identity of Chinese descendants in Indonesia leads and this leads to transformation in the social life of the Chinese descendants in Indonesia up to present, in particular in their identity. This research discusses the transformation of identity among Chinese descendants in Indonesia drawing on the case of Chinese descendants in Lasem. This research applies qualitative method with a case study approach. This research finds that the Chinese descendants in Lasem attempts to construct their new identity through culture hybridization and mimicry that is mingled with the identity of the local community. Through this process, they successfully create a new identity as Chinese-Javanese or wong Lasem that leads them to experience a survival and harmonious life with the local. Since the reforms, this new identity fosters the strong and harmonious interaction between the Javanese and Chinese in Lasem that slowly blurs the identity of the two ethnics.